VIRTUAL MEETINGS UNDER ATTACK: ASSESSING THE LEGAL AND SECURITY RISKS OF ZOOM BOMBING IN THE DIGITAL ERA - Meena, Bheem Singh; Ranjan, Radha; Anand, Shyam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
One example of unforeseen vulnerabilities brought about by the development in virtual meetings as a result of digital era demands is the rise in Zoom bombing attacks. This abstract investigates the security and legal implications of zoom bombing, or the disruptive and unwelcome entry into virtual meetings. We investigate the causes of Zoom bombing and how it affects individuals, organisations, and the broader digital economy. Our study considers both the evolving security measures put in place to counter these assaults and the legal challenges posed by their multinational character. By breaking down these dangers, we highlight the significance of a comprehensive approach to develop virtual meeting places and defend the integrity of digital interactions.